«Translation Studies: An Introduction to the History and Development of (Audiovisual) Translation» - Soler Pardo, Betlem (Revista Linguax (2003-2013), 2013)
Translation is a constant struggle between philological fidelity to the source text and fidelity to the culture of the target language, always bearing in mind that the product must sound natural and credible to the reader. This paper presents an overview of the history of translation; it makes reference to several theoretical models to study translation as a discipline. It alludes to the five approaches originated from the theory to finally focus on the modality of audiovisual translation.
Keywords: translation studies; literal translation; audiovisual translation; Traducción e Interpretación